Prosedur Pemeriksaan MRI Brain pada Kasus Trigeminal Neuralgia di Instalasi Radiologi RSUD Provinsi NTB - Zainal Abidin AR Malasugi; Ni Putu Rita Jeniyanthi; I Made Adhi Mahendrayana (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Research has been conduced on MRI Brain examiation procedures in cases of trigeminal neuralgia at the radiology installation of the NTB Privincial Hospital. The purpose of this study was to determine how the MRI Brain examination procedure in cases of trigeminal neuralgia at the radiology installation of the NTB Provincial Hospital and why the b-FFE sequence was used in the MRI Brain examination of trigeminal neuralgia cases at the Radiologi Installation of the NTB Provincial Hospital. This type of research uses qualitative research with a case study approach to MRI Brain examination in cases of trigeminal neuralgia. This research was conducted in june-july 2023 at the Radiology installation of the NTB Provincial Hospital using observation, intervie and dokumentation methods. The results of the data were processed and reduced by open coding. The results of the study of MRI Brain examination procedures in cases of trigeminal neuralgia at the Radiology Installation of the NTB Provincial Hospital. Starting with patient preparation, the patinet`s position is supine. The sequences used are DWI Axial, T2W TSE Axial, T1W FFE, T2W FLAIR, MRA, T2W TSE Coronal, T2W TSE Sagittal and b-FFE. The reason for using the b-FFE sequence is to show 12 pairs of cranial nerves, one of which is the trigeminal nerve and the b-FFE sequence can be used as a differential diagnosis against other sequences.